Targeting L-arginine/NO/cGMP/KATP pathway by phytochemicals: therapeutic applications and clinical perspectives - Hosseini, Seyede Zahra; Abbaszadeh, Fatemeh; Alavi, Seyede Darya; Gravandi, Mohammad Mehdi; Amirian, Roshanak; Fakhri, Sajad; Echeverría, Javier (Frontiers in Pharmacology, 2025)
BackgroundThe L-arginine/nitric oxide (NO)/cyclic guanosine monophosphate (cGMP)/ATP-sensitive potassium channel (KATP) signaling pathway is a crucial biological pathway that plays a significant role in many physiological processes.PurposeThis study provides a comprehensive overview of this signaling pathway and its therapeutic implications across various diseases, including cardiovascular disorders, metabolic syndromes, and chronic pain conditions. It highlights how natural compounds can effectively influence this essential signaling cascade to help manage different health issues.MethodologyA comprehensive review was conducted to evaluate the effects of phytochemicals on modulating the L-arginine/NO/cGMP/KATP pathway in the treatment of cardiovascular disorders, metabolic syndromes, and chronic pain conditions. The literature review included searches of electronic databases such as Scopus®, PubMed®, and ScienceDirect®, as well as manual searches of reference lists and citations within the authors’ areas of expertise.Results and discussionL-arginine plays a central role in this pathway, which is converted into NO—a potent vasodilator—by nitric oxide synthases, thereby regulating vascular tone and pain sensitivity. The subsequent activation of cGMP and KATP channels further influences cellular function, providing protective effects during ischemic events, supporting cardiovascular stability, helping combat metabolic syndromes, and pain. While traditional pharmacological approaches have shown effectiveness by regulating the pathway, they often come with undesirable side effects. Additionally, emerging evidence supports the role of phytochemicals as promising modulators with therapeutic potential in such conditions.ConclusionPhytochemicals may modulate the L-arginine/NO/cGMP/KATP pathway to treat cardiovascular disorders, metabolic syndromes, and chronic pain conditions.